The synergistic effects of mechanical ventilation and intrauterine inflammation on cerebral inflammation in preterm fetal sheep - Tran, Nhi T.; Somers, Ainsley; Vidinopoulos, Kayla; Azman, Zahrah; Pham, Yen; Zahra, Valerie A.; Chan, Kyra Y. Y.; Hooper, Stuart; Crossley, Kelly; Allison, Beth J.; Galinsky, Robert; Polglase, Graeme R. (Frontiers in Cellular Neuroscience, 2024)
Background: Intrauterine inflammation and the requirement for mechanical ventilation independently increase the risk of perinatal brain injury and adverse neurodevelopmental outcomes. We aimed to investigate the effects of mechanical ventilation for 24 h, with and without prior exposure to intrauterine inflammation, on markers of brain inflammation and injury in the preterm sheep brain.Methods: Chronically instrumented fetal sheep at ~115 days of gestation were randomly allocated to receive a single intratracheal dose of 1 mg lipopolysaccharide (LPS) or isovolumetric saline, then further randomly allocated 1 h after to receive mechanical ventilation with room air or no mechanical ventilation (unventilated control + saline [UVC, n=7]; in utero mechanical ventilation + saline [VENT, n=8], unventilated control + intratracheal LPS [UVC+LPS, n=7]; in utero ventilation + intratracheal LPS [VENT+LPS, n=7]). Serial fetal blood and plasma samples were collected throughout the experimental protocol for assessment of blood biochemistry and plasma interleukin (IL)-6 levels. After 24 h of mechanical ventilation, fetal brains were collected for RT-qPCR and immunohistochemical analyses.Results: LPS exposure increased numbers of microglia and upregulated pro-inflammatory related genes within the cortical grey matter (GM) and subcortical white matter (SCWM) (pLPS<0.05). Mechanical ventilation alone increased astrocytic cell density in the periventricular white matter (PVWM)(pVENT=0.03) but had no effect on pro-inflammatory gene expression. The combination of ventilation and LPS increased plasma IL-6 levels (p<0.02 vs. UVC and VENT groups), and exacerbated expression of pro-inflammatory-related genes (IL1β, TLR4, PTGS2, CXCL10) and microglial density (p<0.05 vs. VENT).This study demonstrates that 24 h of mechanical ventilation after exposure to intrauterine inflammation increased markers of systemic and brain inflammation and led to the upregulation of pro-inflammatory genes in the white matter. We conclude that 24 h of mechanical ventilation following intrauterine inflammation may precondition the preterm brain towards being more susceptible to inflammation-induced injury.